حياة الشيخ عبد الحي الفاروقي ومنهجه في تفسيره "تفسيرالفرقان في معارف القرآن": دراسة تحليلية وصفيةThe Life of Shaikh ‘Abdul Hayy al-Fārūqī and his Approach to his Exegesis “Tafsīr al-Furqān fī M‘ārif al-Qurān”: An Analytical and Descriptive Study (Al-Qamar, 2022)
The Islamic nation has tried to understand the Book of Allah Almighty and know its meanings since the dawn of the true religion. The first to interpret this great book was our Prophet Muhammad himself (May God bless him and grant him peace). Indian subcontinent is very fertile in this discipline. Among the major contributors is Sheikh Abdul Hayy -al-Faruqi. Al-Faruqi, was one of scholars in Quranic Sciences who became famous in the scientific circles and adhered to the Sheikh of India Mahmood al-Hassan al-Deobandi and extracted from the knowledge of his approach, and among the most prominent students of Sheikh Ubaidullah Sindhi and Sheikh Abu al-Kalam Azad. Sheikh Abd al-Hayy al-Faruqi authored different voluminous and short books in the field of Quranic sciences. But his best contribution is the book; “Tafsīr-al- Qurān fi Marif –al-Qurān.” This commentary on Quran has some distinguishing features and distinctive aspects in the art of interpreting the Qur’an following the principles established by Shah Wali Allah in his book “al-fawz al-Kabir fi Usul al-Tafsir”. In this article, the attempts will be made to search his scientific and balanced approach used in his given Quranic exegesis and to explore to what extend he succeeded.
Keywords: Hermeneutics; Shah Wali Allah; Abrogation; Abdul Hayy al-Faruqi; Sub-Continent; Balanced Approach; Exegesis